CAUSALITY TEACHINGS IN PLANNED MURDER CRIMES: (Case Study of Murder with Cyanide Poison) - Tamba, Andi Wiranata; Purnomo, Hadi (Transpublika Publisher, 2024)
The phenomenon of premeditated murder represents a grave criminal offense involving the intentional taking of another person's life through meticulous planning. At the core of any event lies a causal relationship, a fundamental concept known as causality. Causality, in the context of criminal investigations, refers to the cause-and-effect relationship applied to discern the primary factors leading to specific consequences. This research seeks to address the intricate nature of causality within the crime of premeditated murder, particularly examining the series of events identified by law enforcement officials as indicative of a causal relationship. The central challenge in this research pertains to unraveling the specific series employed by law enforcement as a foundation for establishing causality in cases of premeditated murder. Furthermore, the study delves into the question of how responsibility for the criminal act committed by Jessica Kumala Wongso against Victim Wayan Mirna Salihin is attributed based on the principles of causality. Investigating these aspects will contribute to a more comprehensive understanding of the legal mechanisms used to identify and assign accountability in cases of premeditated murder.